If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -20) = x Reorder the terms: 3(-20 + x) = x (-20 * 3 + x * 3) = x (-60 + 3x) = x Solving -60 + 3x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -60 + 3x + -1x = x + -1x Combine like terms: 3x + -1x = 2x -60 + 2x = x + -1x Combine like terms: x + -1x = 0 -60 + 2x = 0 Add '60' to each side of the equation. -60 + 60 + 2x = 0 + 60 Combine like terms: -60 + 60 = 0 0 + 2x = 0 + 60 2x = 0 + 60 Combine like terms: 0 + 60 = 60 2x = 60 Divide each side by '2'. x = 30 Simplifying x = 30
| k^2+8k-2=0 | | y^2+y=3 | | f(x)=x^2-10x-3 | | (9x)-(90-87x)=x | | -3/2(24+6x)=9 | | -2x+x^2=4 | | n^2+2n=7 | | y=-5x+25/2 | | -4*2*(8)= | | 2(a+3)-5(a-y)= | | 96+2x=80-3x*2 | | 96+2x=80-4 | | y=8/3x+4 | | 10x+2y=25 | | 96+2x=80-3x | | p^2-14p+50=0 | | -8x-3(-4+7x)=99 | | -9(y+11)+6= | | 42x-7=2x+9 | | 8(n+3)+5=93 | | 14p+2(5-p)= | | -11(n-2)+8(n+1)=-3(n+10) | | -2d+4d-4=5+3(d-3) | | 5(a+4)-15=-5(a-1) | | (-5)(3-z)= | | 26-3x=25 | | -73x^2+13x+20=0 | | (6+y)(-12)= | | 416=-2x+8(6+6x) | | 8x-3=4x+3 | | 416=-2x+(6+6x) | | z^2-4z=0 |